A New Approach for the Dimensioning of an Air Conditioning System with Cold Thermal Energy Storage. (May 2017) - Mongibello, Luigi; Bianco, Nicola; Caliano, Martina; Graditi, Giorgio
Abstract: In this work, a new approach for the design of air conditioning systems with cold thermal energy storage is described and tested, considering the case study represented by a vapor-compression chiller, coupled with a chilled water storage system, producing cooling for a small multi-apartment building situated in Italy. In the present approach, at the aim of limiting shut-downs and start-ups of the chiller, which involve inefficiencies during transients, and can lead to a drastic reduction of the equipment lifetime, the nominal power of the chiller, and the amount of cooling to be stored are first estimated in a pre-design phase. Successively, the outputs of the pre-design are used to fix the size of the cold storage tank, and to set up the numerical simulation of the cold thermal energy storage system. Finally, the results of the numerical simulation of the cold storage system are used to evaluate the effective size of the chiller. Both the pre-design and the numerical simulations of the cold storage systems have been done by means of home-made numerical tool realized with Simulink. In the paper, the specifications relative to the operational strategy are explored, and the analytical models used for the numerical simulation of the cold storage system relative to the Italian case study are reported in detail. Finally, the results of the pre-design, and of the cold storage system simulations relative to the case study are presented and discussed. The results relative to the Italian case study demonstrates the effectiveness of the present approach in limiting the number of shut-downs and start-ups of the chiller. The present approach can represent a useful tool for the economic optimization of the design of air conditioning systems.